Extremely high-dose insulin requirement in a diabetic patient with psychiatric illness: A case report - Kibret Enyew Belay; Beza Leulseged Ayalew; Abdissa Meherete Etana; Mohammadjavad Ashrafi Mahabadi (SAGE Open Medical Case Reports, 2023)
Severe insulin resistance is defined as the need of insulin requirement of more than two units per kilogram of body weight. It is rarely seen in diabetic patients. Common causes of severe insulin resistance include severe insulin resistance syndromes, drugs, endocrine disorders, factitious causes, lipodystrophy, increased insulin clearance, and impaired insulin absorption. Here, we describe a diabetic patient with major depressive disorder who was prescribed a maximum of 282 units (4.9 units/kg) of insulin a day. However, the cause in this patient was pseudo-resistance to insulin due to the inappropriate use of insulin by the patient. The ability to maintain her glycemia in the target range with lower doses of insulin was confirmed after the patient was admitted to the hospital. It is, therefore, crucial to systematically address any patient who requires an exceptionally high dose of exogenous insulin, starting with technical issues (injection technique, site of administration, or insulin storage), medication adherence, or medication errors.